(untitled) (Research, Society and Development, 2020)
The deinstitutionalization of care for individuals with mental illness is one of the fundamental purposes of Psychiatric Reform in Brazil. Therefore, there is as a central phase, the resizing of the asylum with the argument of the gradual extinction of this circumstance, through the reduction of the number of beds and exchange for therapeutic services that are made available to the community. To identify the repercussions of the deinstitutionalization process for the family member of patients with mental disorders. Scientific articles were searched in the SCIELO, LILACS, BVS-BIREME databases, referring to the theme, with no distinct period. The inclusion criteria for the selection of the sample were: articles published in Portuguese, English, Spanish and European Portuguese that portrayed the theme under study, published and indexed in the referred databases. It can be seen that the greater predominance was given to the qualitative study with 12 articles (80%) due to being researches that mostly interpret qualitative data. It is understood, therefore, that living with the chronic condition becomes, in addition to the difficulties for the family member, a condition that alters the process of being healthy for individuals and groups.